Crystallographic, DFT and docking (cathepsin B) studies on an organotellurium(IV) compound - Caracelli, Ignez; Zukerman-Schpector, Julio; Madureira, Lucas Sousa; Maganhi, Stella H.; Stefani, Hélio A.; Guadagnin, Rafael C.; Tiekink, Edward R. T. * (De Gruyter, 2016)
Some biologically active organotellurium compounds exhibit inhibitory potency against cathepsin B. In this study, an alkyl derivative, viz. [CH3(CH2)2C(I)=C(H)](nBu)TeI2, 1, has been structurally characterised by X-ray crystallography and shown to be coordinated within a C2I2 donor set. When the stereochemically active lone pair of electrons is taken into account, a distorted trigonal bipyramidal geometry results with the iodide atoms in axial positions. Both intra- and inter-molecular Te···I interactions are also noted. If all interactions are considered, the coordination geometry is based on a Ψ-pentagonal bipyramidal geometry. An unusual feature of the structure is the curving of the functionalised C5 chain. This feature has been explored by DFT methods and shown to arise as a result of close C–H···I interactions. A docking study (cathepsin B) was performed to understand the inhibition mechanism and to compare the new results with previous observations. Notably, 1 has the same pose exhibited by analogous biologically active compounds with aryl groups. Thus, the present study suggests that (alkyl)2TeX2 compounds should also be evaluated for biological activity.